The methods of job security system as an instrument for employment rationalization in the management subsystem on the example of a public utility company - Czekaj, Janusz (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The study presents the essence and functions of job security system in the enterprise management subsystem. The classification of methods for determining staffing in the management sphere was discussed. The essence and course of research in the technique of analyzing the labor intensity of functions (tasks) and the internal benchmarking method for job security system were characterized. The results of these methods’ application for employment rationalization in administrative sphere of selected municipal services company were presented.